Rancang Bangun Aplikasi Pencarian Ayat Al-Qur'an Menggunakan Metode Algoritma String Matching Knuth-Morris-Pratt Berbasis Android - Ramdhani, Shubhan; Sukmaaji, Anjik; Sutanto, Teguh (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
Al-Qur'an is a guide and instructions for Muslims, therefore it is necessary to know the contents of the Al-Qur’an. But there are difficulties in finding a Qur'anic verse that corresponds to the topic that you want to search. One of these factors is there are wide variety of topics contained in a surah and surah have a different topics, while there are 114 surah and 30 juz in 6236 surat in the Qur'an, so if we search manually it will take a lot of time. So we built an application search verses of the Quran by using the Knuth-Morris-Pratt algorithm based on Android. The algorithm used to perform string matching exactly with the order of the characters in the string are matched and highly effective in searching a pattern or patterns of words. This algorithm will perform matching keywords entered by the user with the translation of the Qur’an, and displays the results of our search according to keywords. Based on the test that have been conducted, Knuth-Morris-Pratt algorithms in the process of finding verses of the Qur'an on this application has an average accuracy rate of verse produced is 60% and the rate of speed of searching is 1,25 seconds.